Study on impact resistance of precast light-weight concrete sandwich panels. (January 2023) - Yang, Yanmin; Ge, Zesen; Li, Yongqing; Xiong, Ying; Yuan, Qi
Abstract: To investigate the dynamic impact resistance of precast lightweight sandwich panels (PLCSP) composed of non-sintered coal ash ceramsite concrete and self-developed thermal blocking shear connectors, drop hammer impact tests with different impact energy were carried out in the central area of the exterior wythe. The dynamic response of PLCSP under different steel fibers content, wythe thickness, and the different number of shear connectors was compared and analyzed. The numerical simulation was carried out by LS-DYNA. The results show that 2% volume fraction of steel fibers enhance the stiffness of the panel by improving the overall impact toughness, while the increase in wythe thickness slows down the panel amplitude to enhance the stiffness. The exterior wythe of the PLCSP has penetrated failure, and the failure mode of the interior wythe changes from bending failure to collapse failure with the increase of the number of shear connectors. Therefore, the arrangement spacing of shear connectors can be appropriately reduced to reduce the risk of collapse failure. The ratio of maximum displacement and residual displacement of the panel under different impact energies ranged from 3.37 to 5.94, and the maximum erosion depth of the hammer was twice the displacement of the bottom of the panel, indicating that the unique sandwich structure and material of the PLCSP have good impact resistance. The research results can provide reference for the design and application of PLCSP.